Evaluasi Kualitas Airtanah Sebagai Sumber Air Minum Di Sekitar Pabrik Gula Camming Kabupaten Bone - Qaiyimah, Dinil; Sukri, Irwansyah; Jeddah Yanti (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Groundwater quality is a critical factor in ensuring the availability of safe drinking water for communities. This study aims to evaluate the feasibility of shallow groundwater quality in dug wells around the Camming Sugar Factory. The evaluation results are used to analyze the influence of land use on groundwater quality. This research employs a quantitative method with a descriptive approach. The data obtained are interpreted using a scoring method based on Sturges' rule to classify groundwater quality into several categories. Sampling was conducted to measure the physical, chemical, and biological parameters of shallow groundwater. The results were compared with drinking water quality standards issued by the Ministry of Health of the Republic of Indonesia. The results of the analysis show that the quality of groundwater in Wanuawaru Village is generally safe for human consumption based on physical parameters, with temperatures between 27 and 29°C, color values of 5 to 15 TCU, turbidity of 0.28 to 10.1 NTU, and TDS of around 900 mg/l. However, for chemical parameters, it was found that nitrate levels were below the acceptable limit. Conversely, the iron concentration in Sample 2 exceeded the permissible limit, and water hardness levels in all three samples were significantly higher than the standard. The pH levels fell within the acceptable range for drinking water, and BOD values were well below the threshold. Biological analysis indicated that all samples contained E. coli bacteria exceeding acceptable limits, signaling significant biological contamination. These findings highlight the need for routine monitoring and special attention to iron concentrations and water hardness. Additionally, the implementation of standard-compliant septic tank construction is necessary to prevent bacterial contamination, ensuring that shallow groundwater in the study area meets the standards for drinking water sources.